2023
DOI: 10.7759/cureus.39636
|View full text |Cite
|
Sign up to set email alerts
|

Prone Vs. Supine Position Ventilation in Intubated COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: Whether prone positioning of patients undergoing mechanical ventilation for COVID-19 pneumonia has benefits over supine positioning is not clear. We conducted a systematic review with meta-analysis to determine whether prone versus supine positioning during ventilation resulted in different outcomes for patients with COVID-19 pneumonia. We searched Ovid Medline, Embase, and Web of Science for prospective and retrospective studies up through April 2023. We included studies that compared outcomes of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another meta-trial spanning six countries indicated that awake-prone positioning reduced treatment failure and intubation needs in hypoxemic respiratory failure cases without significant mortality improvement ( 8 ). Conversely, a meta-analysis encompassing mechanically ventilated patients showed no reduction in mortality, intensive care unit (ICU) stay, or mechanical ventilation duration in prone positioned patients ( 9 , 10 ). Some of the studies included in this meta-analysis had limitations that were addressed ( 11 - 13 ).…”
mentioning
confidence: 99%
“…Another meta-trial spanning six countries indicated that awake-prone positioning reduced treatment failure and intubation needs in hypoxemic respiratory failure cases without significant mortality improvement ( 8 ). Conversely, a meta-analysis encompassing mechanically ventilated patients showed no reduction in mortality, intensive care unit (ICU) stay, or mechanical ventilation duration in prone positioned patients ( 9 , 10 ). Some of the studies included in this meta-analysis had limitations that were addressed ( 11 - 13 ).…”
mentioning
confidence: 99%